Learning Techniques and Strategies to Produce Stand-Up Comedians - Trisna Pradita Putra (Institut Seni Indonesia Yogyakarta, 2025)
Comedian is a profession that has been recognized since the 18th century. Although the comedian profession has been recognized, formal education or training to become a humanist and competent comedian is still very rarely carried out. “Pecahkan” is a stand-up comedy educational institution that consistently organizes training to become a solo comedian. The success of the